Masculinity, Class and Music Education Boys Performing Middle-Class Masculinities through Music - Hall, Clare (Palgrave Studies in Gender and Education, 2018)
This book offers a provocative sociological examination of masculinity, class and music education within the context of a unique and fascinating culture: the classical musical world of choirboys. The myriad cultural meanings embodied in the 'boy voice' are unravelled through compelling musical narratives of young choirboys, their mothers, and their teachers. The book investigates how boys negotiate dominant gender-class discourses and the various pedagogies involved in producing middle-class masculinities during primary school and early years contexts. Drawing on the theoretical resources of Bourdieu to develop the concept of 'musical habitus', the continued symbolic distinction of the choirboy is analysed in order to better understand how culture is simultaneously reproduced and evolving through music. This interdisciplinary work at the juncture of pedagogy and culture will appeal to social science researchers, educators and arts practitioners interested in the sociocultural dynamics of music.